STUDY OF VIRULENCE FACTORS GENES AND ANTIBIOTICS SUSCEPTIBILITY OF STAPHYLOCOCCUS AUREUS ISOLATED FROM WOMAN WITH BREAST ABSCESS - Ghaly yousif, Maitham; Hassan almayahi, Mohammed (Al-Qadisiyah Journal of Pure Science, 2019)
The aim of this study is isolating and diagnosing Staphylococcus aureus from breast abscesses in women using some morphological , serological and molecular methods as well testing the sensitive of isolates to antibiotic and molecular detection of virulence and resistant gene . Samples were collected from women with breast abscesses. The results of the biochemical tests,Api Staph and MASSTAPHAP explained 23 isolates of S.aureus bacteria Molecular diagnosis using 16srRNA gene confirmed morphological and serological diagnosis for all (23) isolates (100%) with 27% of the total of eighty –Five clinical samples. The results of the present study showed that the most age group exposed to S.aureus infection was (21 -30) years with 39.3%. The most affected women were lactating woman (29.31%). The percentage, especially for non-lactating women with breast mastitis and breast cancer, was 33.3%. Antibiotic sensitivity test using disk diffusion method showed that the sensitivity of the S. aureus isolates to antibiotic was higher than the resistance . Molecular detection using PCR technique showed that 21 isolates of the Luks gene (91.3%) and 20 isolates had a blaz gene (86.9%) .